Interstitial Lung Abnormalities and Reduced Exercise Capacity - Doyle, Tracy J.; Washko, George R.; Fernandez, Isis E.; Nishino, Mizuki; Okajima, Yuka; Yamashiro, Tsuneo; Divo, Miguel J.; Celli, Bartolome R.; Sciurba, Frank C.; Silverman, Edwin K.; Hatabu, Hiroto; Rosas, Ivan O.; et al. (American journal of respiratory and critical care medicine, 2012)
The relationship between interstitial lung abnormalities (ILA) and exercise capacity has not been comprehensively evaluated. To assess the validity of the 6-minute walk test in subjects with ILA, and to examine the association between ILA and 6-minute walk distance (6MWD). Spearman correlation coefficients were used to assess the strength of the relationships between 6MWD and relevant measures of dyspnea, health-related quality of life, and pulmonary function in a cohort of 2,416 people who smoke from the COPDGene study. Unadjusted and adjusted linear and logistic regression models were used to assess the strength of the association between ILA and 6MWD. In all subjects, and in those with ILA, 6MWD in COPDGene was associated with relevant clinical and physiologic measures. The mean 6MWD in COPDGene subjects with ILA was 386 m (SD, 128 m), and 82% and 19% of subjects with ILA had 6MWDs less than or equal to 500 and 250 m, respectively. ILA was associated with a reduced 6MWD in univariate (-30 m; 95% confidence interval, -50 to -10; P = 0.004) and multivariate models (-19 m; 95% confidence interval, -33 to -5; P = 0.008). Compared with subjects without ILA, subjects with ILA had an 80% and 77% increase in their odds to have a walk distance limited to less than or equal to 500 and 250 m, respectively. Although these findings were dependent on ILA subtype, they were not limited to those with COPD. Our study demonstrates that ILA is associated with measurable decrements in the 6MWD of people who smoke. Clinical trial registered with www.clinicaltrials.gov (NCT 00608764).